Hybrid Bat Algorithm for Balancing Load in Cloud Computing - Sharma, Shabnam; Sahil Verma, Dr.; Kiran Jyoti, Dr.; Kavita, Dr. (International Journal of Engineering and Technology, 2018)
Swarm Intelligence is proven to be beneficial for solving many problems including knapsack problem, minimum spanning tree, planning problems, routing, load balancing and many more. Here, the focus of the work is on bat algorithm. Due to astonishing feature of echolocation, bat algorithm has drawn researcherâ€™s attention in past years. It is applicable in solving different problems such vehicle routing optimization, time-tabling in railway optimization problems, load balancing in cloud computing etc. The main objective of this work is to propose a technique balancing the load among virtual machines in cloud computing environment.Â